A Sociological Analysis of The Ideal Husband by Oscar Wilde - Helmita Helmita; Haicha Fadella (Jurnal Ilmiah Langue and Parole, 2018)
This research is a about the marriage crisis is reflected in Oscar Wilde's An Ideal Husband drama, what strategy is employed to maintain a marriage, and why did Oscar Wilde give concern in the marital crisis. The purpose of this study is (1) To describe the marital crisis illustrated reflected in the drama An Ideal Husband by Oscar Wilde (2) To explain the strategy in maintaining a marriage (3) and to reveal the reason why Oscar Wilde gave concern in the marital crisis. The approach used is a sociology approach that the discusses an external aspects of a drama. The theory used in this research is the theory sociology of literature according to Alan Swingewood and Diana Laurenson which states that conflict in life, especially in every househould, is a reflection of the life everyone. This study employs the qualitative method. The object of the study is An Ideal Husband play written by Oscar Wilde. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the play script itself and the secondary data sources are script text and some references related to the research. The technique of the data collection is note-taking. The technique of the data analysis is descriptive analysis.The first, marital crisis is illustrated in Oscar Wilde’s An Ideal Husband play are when a woman marries with a man who have important position in their work, inability someone to accept reality from their spouse in past, no children in the family, jealousy, and wife’s opinion that her husband is ideal. The second, the strategies are employed to maintain a marriage are introspection, making agreement between husband and wife, and accepting reality. The third, Oscar Wilde gave concern in marital crisis because he wants to criticize the England society in that era especially in upper class society that hypocrite for many cases.